Impact Of Digital Technologies On Pedagogical Practice In Primary Education - Quadros-Flores, Paula (2019)
Rare are the teachers who have never used information and communication technologies (ICT) in an educational context. We intend to know the impact of the inclusion of ICT in the learning process by listening to primary teachers in service and students in an internship situation, the latter in the scope of initial teacher training. With regard to in-service teachers, a case study of a quantitative and qualitative nature was chosen in the Porto region in 2012. The analysis of a question of a questionnaire survey of about 1300 teachers, teaching in public and private institutions in the Porto region, is presented. Of these, 188 referred to perform good practices with digital technologies being eleven selected for interview, for which the analysis of the good practices referred to is presented. With regard to trainee students, in the scope of initial teacher training, 15 reflective narratives selected from two professional masters were analyzed. The analysis of the questionnaire question allowed to verify the impact of ICT in educational practices and the triangulation of data allowed on the one hand to clarify the conception of good practices and to find the principles of the same ones, on the other hand to verify the evolution of educational practices in terms of the selected resources and methodologies. We intend to contribute to a reflection on the impact of ICT in primary education and on the responses that training institutions can give on this issue.